Analysis of Deixis in “The Greatest Showman (2017)” Movie and Its Contribution to Language Teaching - Pratiwi, Anisa; Suwandi, Suwandi; Yosephin, Maria (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study analyzes the types and contributions of deixis in The Greatest Showman (2017) movie script using Levinson’s (1983) theory. Employing a qualitative descriptive approach, data were collected by examining the movie script and classifying deixis into five categories: person, time, place, discourse, and social deixis. The findings indicate that person deixis is the most dominant type, appearing 619 times (65%), followed by place deixis (11%), social deixis (9%), discourse deixis (8%), and time deixis (7%). The study highlights the role of deixis in understanding contextual meaning in language use. Moreover, deixis analysis in movies can enhance English language learning by providing contextualized examples of pragmatic expressions. This study suggests that future research compare deixis usage in different movie genres to deepen the understanding of deixis functions in communication.